2013
DOI: 10.1038/ijo.2013.4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond sleep duration: distinct sleep dimensions are associated with obesity in children and adolescents

Abstract: ObjectiveShort sleep duration is recognized as a significant risk factor in childhood obesity; however, the question as to how sleep contributes to the development of obesity remains largely unknown. The majority of pediatric studies have relied on sleep duration as the exclusive measure of sleep; this insular approach may be misleading given that sleep is a dynamic multidimensional construct beyond sleep duration, including sleep disturbances and patterns. While these sleep dimensions partly overlap, it is ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(81 citation statements)
references
References 58 publications
7
67
0
1
Order By: Relevance
“…Previous published studies have used this item to assess subjective sleep quality in youth (e.g., Jarrin et al, 2013). The Child's Sleep Habits Questionnaire (CSHQ) is a 35-item parent-report questionnaire that assesses sleep problems in children over the past month (Owens et al, 2000).…”
Section: Perceived Stress-thementioning
confidence: 99%
See 1 more Smart Citation
“…Previous published studies have used this item to assess subjective sleep quality in youth (e.g., Jarrin et al, 2013). The Child's Sleep Habits Questionnaire (CSHQ) is a 35-item parent-report questionnaire that assesses sleep problems in children over the past month (Owens et al, 2000).…”
Section: Perceived Stress-thementioning
confidence: 99%
“…Polysomnography-derived longer sleep onset latency, shorter sleep duration, lower sleep efficiency, and higher sleep fragmentation are related to higher morning and daytime cortisol levels (Hatzinger et al, 2008(Hatzinger et al, , 2010. While both poor sleep quality and short sleep duration have been linked to a disrupted diurnal cortisol profile, evidence suggests that sleep quality may be a marker of slow-wave sleep, a sleep stage thought to have important inhibitory effects on cortisol secretion (Jarrin et al, 2013;Kaneita et al, 2007). It is plausible that the quality of sleep may have greater impact on the diurnal cortisol profile than the quantity of sleep.…”
mentioning
confidence: 99%
“…The sleep-obesity association may be stronger in boys than in girls [22]. Poor sleep quality, other sleep disturbances and delayed sleep phase also predict increased adiposity independently of total sleep duration and other confounders [24]. These studies reveal a consistent, moderate-strength association between chronic insufficient sleep and obesity in children and adolescents, with smaller studies indicating a strong association between fragmented or poor-quality sleep and adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep problems are associated to obesity (Gupta, Mueller, Chan, and Meininger 2002;Knutson 2011;Jarrin, McGrath, and Drake 2013), poor nutrition (Beebe, Simon, Summer, Hemmer, Strotman, and Dolan 2013;Grandner, Jackson, Gerstner, and Knutson 2013;Hogenkamp et al 2013), and increased cardiovascular risk (Buxton and Marcelli 2010). A cross-sectional study of 1101 Brazilian adult subjects (20-80 years old) found a depression prevalence of 10.9% and was significantly higher among housewives, unemployed individuals, and those with low income and education (Castro et al 2013).…”
Section: Sleepmentioning
confidence: 99%